DNA Framework Nanomachines for Translational Medicine - Lixuan Lin; Kai Jiao; Linjie Guo; Chunhai Fan; Jiang Li (Accounts of Materials Research, 2026)
Conspectus Precise treatment of intractable diseases such as cancer using nanomachines epitomizes a grand aspiration in biomedical science. Among the various approaches, nanomachines offer a promising route with molecular precision. Despite notable progress in recent decades, clinical translation of such machines remains constrained by the complexity of the physiological environment. Multitiered biological barriers limit their targeted distribution across human-scale distances, while intricate bionano interactions raise substantial challenges concerning in vivo efficacy, targeting specificity, and biocompatibility. DNA, the primary carrier of genetic information, is now repurposed to exhibit functions that extend beyond the central dogma. Leveraging its programmable and predictable self-assembly, DNA has become a transformative material for engineering precise nanoscale structures, molecular circuits, and functional nanomachines, demonstrating increasing translational potential in biomedicine. In this Account, we review recent advances in the design of DNA framework nanomachines. We first introduce programmable DNA frameworks, which serve as versatile platforms for the precise, nanoscale spatial organization of functional modules, resulting in emergent properties and functionalities differing from conventional DNA molecules. We next describe how DNA structures generate mechanical outputs, such as structural reconfiguration, establishing the foundation for nanomachines. Meanwhile, DNA computation, driven by molecular reactions, has demonstrated capabilities including Boolean logic, pattern recognition, and temporally resolved discrimination of multiple inputs. We discuss the integration of mechanical actuation and DNA computation into intelligent nanomachines, which can sense environmental cues, process complex environmental information and produce structural-functional outputs. Importantly, these structures can be engineered to traverse in vivo hierarchical biological barriers, from tissues and cells to subcellular compartments. We discuss how DNA framework structures overcome like-charge attraction with cell membranes via corner-attack modes and caveolin-mediated uptake, penetrate skin and ocular barriers in a size-dependent manner, and achieve renal or lymphatic targeting. Recent investigations have elucidated critical interactions between these nanostructures and multilevel biological interfaces, such as immune modulatory effects, thereby illuminating their underlying mechanisms and advancing clinical translation prospects. We propose that topical drug delivery based on DNA frameworks is approaching clinical translation. In the near term, plausible directions include systemic delivery applications such as kidney disease diagnosis and treatment, as well as vaccination against pathogens and tumors. Looking ahead, intelligent DNA framework nanomachines may implement automated, adaptive, multidimensional theranostics, advancing the vision of precision medicine. We discuss several persistent challenges, including structural and functional instability in vivo, potential biosafety concerns, and substantial gaps between animal models and human patients. We also outline possible solutions, such as AI-assisted design, microfluidics-based manufacturing, and humanized models.